2010
DOI: 10.1098/rspb.2010.1560
|View full text |Cite
|
Sign up to set email alerts
|

Translating environmental gradients into discontinuous reaction norms via hormone signalling in a polyphenic butterfly

Abstract: Polyphenisms-the expression of discrete phenotypic morphs in response to environmental variation-are examples of phenotypic plasticity that may potentially be adaptive in the face of predictable environmental heterogeneity. In the butterfly Bicyclus anynana, we examine the hormonal regulation of phenotypic plasticity that involves divergent developmental trajectories into distinct adult morphs for a suite of traits as an adaptation to contrasting seasonal environments. This polyphenism is induced by temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
148
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(170 citation statements)
references
References 36 publications
16
148
6
Order By: Relevance
“…Therefore I studied population dependent differences in expression profiles of genes belonging to the circadian clock and the insulin signaling pathway (study III). Also hormones could be likely candidates in driving population dependent divergence, since they sit on key regulatory points in the pathways producing differing phenotypes (Zera 2007, Oostra et al 2010. Additionally, I study whether there are population dependent differences in susceptibility to manipulations of hemolymph JH titers by manipulating them positively or negatively through topical applications (study IV).…”
Section: Aims Of the Thesismentioning
confidence: 99%
“…Therefore I studied population dependent differences in expression profiles of genes belonging to the circadian clock and the insulin signaling pathway (study III). Also hormones could be likely candidates in driving population dependent divergence, since they sit on key regulatory points in the pathways producing differing phenotypes (Zera 2007, Oostra et al 2010. Additionally, I study whether there are population dependent differences in susceptibility to manipulations of hemolymph JH titers by manipulating them positively or negatively through topical applications (study IV).…”
Section: Aims Of the Thesismentioning
confidence: 99%
“…Although the genetic, developmental, and hormonal control of seasonal polyphenism are becoming increasingly understood, there are relatively few studies that examine the evolution of the pattern elements of seasonal forms (Rountree and Nijhout 1995;Monteiro et al 2015;Oostra et al 2011). Therefore we asked the following questions: (a) How do wing phenotype elements such as shape and pattern differ between seasonal forms?…”
mentioning
confidence: 99%
“…Titers of 20E measured in the early pupal stage showed small differences between the seasonal form genetic mimics, and 20E injections into the dry season form mimic, which had a natural slower increase of 20E during the pupal stage, showed small (albeit significant) increases in eyespot size toward the phenotype of wet season forms (Koch et al 1996). Later work, however, showed that these 20E titer differences observed between WS and DS form genetic mimics could more readily explain variation in pupal stage duration than eyespot size differences (Oostra et al 2011).…”
Section: Physiological Mechanisms Of Eyespot Plasticitymentioning
confidence: 96%
“…This period shows variation in timing of 20E titers in the seasonal form "genetic mimics" as well as in the actual seasonal forms (Mateus et al 2014;Oostra et al 2011). In particular, titers of 20E are low during the first 24 h (WS) (and 48 h in the DS) after pupation, which is the developmental window believed to be important for eyespot ring differentiation at high temperatures (French and Brakefield 1992;Brunetti et al 2001b).…”
Section: Physiological Mechanisms Of Eyespot Plasticitymentioning
confidence: 99%